A case report of a patient with primary familial brain calcification with a PDGFRB genetic variant - Al Ali, Jamal; Yang, Jessica; Phillips, Matthew S.; Fink, Joseph; Mastrianni, James; Seibert, Kaitlin (Frontiers in Neurology, 2023)
Fahr’s disease, or primary familial brain calcification (PFBC), is a rare genetic neurologic disease characterized by abnormal calcification of the basal ganglia, subcortical white matter and cerebellum. Common clinical features include parkinsonism, neuropsychiatric symptoms, and cognitive decline. Genes implicated in Fahr’s disease include PDGFB, PDGFRB, SLC20A2, XPR1, MYORG and JAM2. We present the case of a 51-year-old woman who developed subacute cognitive and behavioral changes primarily affecting frontal-subcortical pathways and parkinsonism in association with extensive bilateral calcifications within the basal ganglia, subcortical white matter, and cerebellum on neuroimaging. Relevant family history included a paternal aunt with parkinsonism at age 50. Normal parathyroid hormone and calcium levels in the patient’s serum ruled out hypoparathyroidism or pseudohypoparathyroidism as causes for the intracranial calcifications. Genetic panel sequencing revealed a variant of unknown significance in the PDGFRB gene resulting in a p.Arg919Gln substitution in the tyrosine kinase domain of PDGFRB protein. To our knowledge this is the first report of a p.Arg919Gln variant in the PDGFRB gene associated with PFBC. Although co-segregation studies were not possible in this family, the location of the variant is within the tyrosine kinase domain of PDGFRB and pathogenicity calculators predict it is likely to be pathogenic. This report adds to the list of genetic variants that warrant functional analysis and could underlie the development of PFBC, which may help to further our understanding of its pathogenesis and the development of targeted therapies for this disorder.